Clinical and Therapeutic Significance of Various Heat Shock Proteins: Life Sciences-Biotechnology For Prospective Medical Science - Maheswara Reddy Mallu; Sree Rama Chandra Karthik Kotikalapudi; Renuka Vemparala; Chandana Agaarapu; Siva Reddy Golamari (International Journal of Life Science and Pharma Research, 2022)
The purpose of this study was to explore the different roles of heat shock proteins especially in immunity and infections. Heat shock proteins were discovered 56 years ago, and much of the work has focused on the role of these proteins that play in protecting cells from stress. Heat shock proteins are highly conserved class of proteins present in all species from bacteria to humans. Several experimental studies have been successful in pointing to the role of heat shock protein as a clinical biomarker and therapeutic target in a variety of diseases. It will also highlight features of HSP family, and will discuss future implications of HSPs in the diagnosis and prognosis of clinical and therapeutic significance. The development of membrane-interacting drugs that modify specific membrane domains, modulating heat shock response, may also be of significant therapeutic benefit. These proteins function as molecular chaperones, assisting in the refolding of misfolded proteins or their elimination if they become irreversibly damaged. Proteomic studies have identified several different HSPs in various disease types that may be clinical biomarkers or molecular targets for various therapies.